Social Criticism in The Novel Lebih Senyap Dari Bisikan by Andina Dwifatma: Kritik Sosial dalam Novel Lebih Senyap dari Bisikan Karya Andina Dwifatma - Muhammad Safar; Irianto Ibrahim; La Tike; Nur Israfyan Sofian (CASA CENDEKIA MEDIA, 2026)
Literary works provide not only aesthetic experience but also a medium for criticizing unequal social realities. This study aims to describe forms of social criticism in Andina Dwifatma's novel Lebih Senyap dari Bisikan [Quieter than a Whisper] and to explain their contribution to sociological literary studies and literature learning. The research employed a descriptive qualitative method using a sociology of literature approach. The primary data source was the 2021 Gramedia Pustaka Utama edition of Lebih Senyap dari Bisikan, and the data consisted of narrative units, dialogues, and events representing social criticism. The data were collected through intensive reading, note-taking, coding, classification, and interpretive validation based on Soekanto's categories of social problems as adapted in literary sociology. The findings reveal 23 units of social criticism distributed into eight categories: family disorganization 7 units (30.43%), education 4 (17.39%), poverty 3 (13.04%), religion 3 (13.04%), youth in modern society 3 (13.04%), crime 1 (4.35%), bureaucracy 1 (4.35%), and environmental issues 1 (4.35%). The most dominant criticism concerns family vulnerability, particularly gendered inequality, reproductive pressure, domestic violence, and failed marital communication. The study concludes that the novel does not merely portray household problems but also reveals the interconnection among poverty, social institutions, religion, education, modern culture, and the female body. Its contribution lies in strengthening sociological readings of contemporary Indonesian prose and offering a socially responsive model for literature learning materials.